2010
DOI: 10.4021/gr2010.02.165w
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Liver Trauma: Operative or Conservative Management

Abstract: BackgroundThe liver is one of the most frequently damaged organs when abdominal trauma occurs. Currently, a conservative management constitutes the treatment of choice in patients with hemodynamic stability. The aim of this study is to evaluate the results of an operative and conservative management of 143 patients with liver injury treated in a single institution.MethodsA retrospective study of the patients admitted with the diagnosis of liver trauma was performed from 1992-2008. The patients were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 27 publications
2
21
0
3
Order By: Relevance
“…A similar study from Spain [18] described 143 patients admitted between 1992 and 2008 and found that surgery was required in 38% with 15% of the SNOM group eventually requiring operation. Haemodynamic instability was the main indication for operation following failure of SNOM in 9 out of 11 patients.…”
Section: Civilian Liver Traumamentioning
confidence: 95%
See 1 more Smart Citation
“…A similar study from Spain [18] described 143 patients admitted between 1992 and 2008 and found that surgery was required in 38% with 15% of the SNOM group eventually requiring operation. Haemodynamic instability was the main indication for operation following failure of SNOM in 9 out of 11 patients.…”
Section: Civilian Liver Traumamentioning
confidence: 95%
“…The numbers involved were small and we would not advocate this approach for all unstable trauma cases. There is also emerging literature about the pitfalls of multiple scans delaying definitive treatment and the additional radiation exposure increasing the risk of carcinogenesis in trauma patients [18].…”
Section: Patient Selection For Operative Managementmentioning
confidence: 99%
“…In another study Bernardo et al (n=143) majority (83.6%) of patients were males. 12 The incidence of abdominal trauma in the male population is higher because in our country males are the leaders of the family and hence lead a more active life and undergo more outdoor activities. Similar demographic data have been reported in other studies with most injuries affecting males and being incurred due to blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been published in other studies Bernardo et al and Croce et al with most injuries due to road traffic accidents. 12,24 Vehicular accidents occur more frequently because every year there is increase in number of vehicles on road, poor maintenance of road, general public and drivers not following the rules and regulations, nonuse of seat belts, helmets, airbags in vehicles and lack of motivation and education in general-assault due to hit or by animal also is significant mode of trauma in rural parts of the country were run over or goring by a bullock is quite common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation